Introductory Chemistry - Ball, David W.; Key, Jessie A.; Open Textbook Library (Open Textbook Library, 2014)
The goal of this textbook is not to make you an expert. True expertise in any field is a years-long endeavor. Here I will survey some of the basic topics of chemistry. This survey should give you enough knowledge to appreciate the impact of chemistry in everyday life and, if necessary, prepare you for additional instruction in chemistry.
Chapter 1. What is Chemistry -- Chapter 2. Measurements -- Chapter 3. Atoms, Molecules, and Ions -- Chapter 4. Chemical Reactions and Equations -- Chapter 5. Stoichiometry and the Mole -- Chapter 6. Gases -- Chapter 7. Energy and Chemistry -- Chapter 8. Electronic Structure -- Chapter 9. Chemical Bonds -- Chapter 10. Solids and Liquids -- Chapter 11. Solutions -- Chapter 12. Acids and Bases -- Chapter 13. Chemical Equilibrium -- Chapter 14. Oxidation and Reduction -- Chapter 15. Nuclear Chemistry -- Chapter 16. Organic Chemistry -- Chapter 17. Kinetics -- Chapter 18. Chemical Thermodynamics
In English.
Description based on print resource
Keywords: Science -- Textbooks; Chemistry -- Textbooks